2021
DOI: 10.3390/antibiotics10081011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Natural Antioxidants against SARS-CoV-2? Insights from the In-Silico World

Abstract: The SARS CoV-2 pandemic has affected millions of people around the globe. Despite many efforts to find some effective medicines against SARS CoV-2, no established therapeutics are available yet. The use of phytochemicals as antiviral agents provides hope against the proliferation of SARS-CoV-2. Several natural compounds were analyzed by virtual screening against six SARS CoV-2 protein targets using molecular docking simulations in the present study. More than a hundred plant-derived secondary metabolites have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 116 publications
(117 reference statements)
0
25
0
Order By: Relevance
“…The inhibitory effect of luteolin against the M pro is recently confirmed [146]. Fayyaz et al screened several flavonoids and identified three potentially active flavonoids, whose activities against SARS-CoV-2 M pro were in the order of rhodiolin > baicalin > silymarin based on their binding energy (−9.05, −8.85, −8.71 kcal/mol respectively) and dissociation constant (0.23, 0.33, 0.41 µm, respectively) using molecular docking and simulation studies [147]. Thioflavonol also inhibits Mpro [148] along with other flavonoids such as apigenin, daidzein, quercetin, kaempferol, luteolin, epigallocatechin, and kaempferol using molecular docking and simulation analysis [104].…”
Section: Flavonoids Against Sars-cov-2 M Promentioning
confidence: 78%
See 3 more Smart Citations
“…The inhibitory effect of luteolin against the M pro is recently confirmed [146]. Fayyaz et al screened several flavonoids and identified three potentially active flavonoids, whose activities against SARS-CoV-2 M pro were in the order of rhodiolin > baicalin > silymarin based on their binding energy (−9.05, −8.85, −8.71 kcal/mol respectively) and dissociation constant (0.23, 0.33, 0.41 µm, respectively) using molecular docking and simulation studies [147]. Thioflavonol also inhibits Mpro [148] along with other flavonoids such as apigenin, daidzein, quercetin, kaempferol, luteolin, epigallocatechin, and kaempferol using molecular docking and simulation analysis [104].…”
Section: Flavonoids Against Sars-cov-2 M Promentioning
confidence: 78%
“…On the other hand, naringin inhibits the spike glycoprotein more effectively with binding energy −9.8 kcal/mol compared to standard drug dexamethasone with the binding energy of −7.9 kcal/mol [156]. Fayyaz et al described potentially active flavonoids, whose activities against SARS-CoV-2 spike protein were in the order of rhodiolin > hesperidin (with active site 1) > hesperidin (with active site 2) > silyhermin based on their binding energy (−8.68, −8.53, −8.18, −8.05 kcal/mol, respectively) and dissociation constant (0.43, 0.56, 1.01, 1.25 µm respectively) [147]. The authors showed that hesperidin could bind to two different active sites on the spike glycoprotein with different binding energies.…”
Section: Flavonoids Against Sars-cov-2 Spike Glycoproteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Several in silico studies suggested that flavonoids such as EGCG, hesperidin, oleuropein, and myricetin could be used as an alternative therapy for SARS-CoV-2 (Peterson, 2020;Khaerunnisa et al, 2020;Meneguzzo et al, 2020;Adem et al, 2020;Rehman MFu et al, 2021). Considering the promising results of the in silico studies, the potential therapeutic and prophylactic effects of plant-isolated natural flavonoids should be further investigated by in vitro studies to reveal their efficiency.…”
Section: Discussionmentioning
confidence: 99%